ANALYSIS OF THE POLISH FARMERS INVESTMENT ACTIVITY SUPPORTED BY PUBLIC FUNDS - Spychalski, Grzegorz (Acta Scientiarum Polonorum. Oeconomia, 2003)
Paper presents analysis of investment activity among Polish farmers according to the statistical data coming from governmental Agency for Restructuring and Modernisation of Agriculture. Moreover demand for investment credit was analysed and important state policy measure – subsidies to interest rate were described. Paper is ended with prognostic and application conclusions for the agricultural policy in Poland.